Legal aspects of the environmental use of sewage sludge - Wieremiej, Wiesław; Kuziemska, Beata; Pieniak-Lendzion, Krystyna; Trębicka, Joanna; Wyrębek, Henryk (Management and Administration Journal, 2023)
Multi-annual prognoses on the amount of sewage sludge assume a systematic increase in volume. The data released by the Central Statistical Office indicates that the volume of municipal sewage sludge generated in 2011 was 519.2 thousand Mg DM while, according to predictions byKPGO, it will reach 746.0 thousand Mg DM in 2022 – yielding an increase of 43.7% in comparison with the current level. The issue of sewage sludge has been included in the National Programme of Waste Management, which assumes by 2022: a reduction in sludge disposal; an increase in the volume of municipal sewage sludge processed before release into the environment and of thermally processed sludge and maximization of the degree to which biogenic substances found in sludge areused while meeting all requirements of sanitary and chemical safety. Since sewage sludge contains organic matter as well as many micro- and macroelements, it may constitute a valuable fertilizer. Limitations of its environmental usage are related to an excessive (in some types of sludge) content of heavy metals and pathogenic microorganisms. Detailed guidelines on the environmental use of sewage sludge are specified in the Waste Act of 14 December 2012.